A Barycenter Control Method for the Bioinspired Forest Chassis Robot on Slope. (30th April 2021) - Sui, Tingting; Liu, Jinhao; Wang, Jianli; Zhang, Jianting
Abstract : To improve the stability of forestry chassis on the slope, a chassis-installed barycenter adjustable mechanism (BAM) is designed, and the control method of the counterweight is proposed to make the chassis barycenter move suitably to achieve the design purpose. The kinematic analysis of BAM is carried out, and the relationship between the translation, rotation, and vertical displacement of counterweight and the chassis barycenter is calculated. Furthermore, the variation curves obtained in Matlab show the barycenter can translate 100 mm, rotate from 0 to 360 degrees, and lower about 180 mm in the vertical direction. Adams is adopted to complete the kinematics simulation of the chassis, indicating that the control method can effectively adjust the barycenter position. Finally, experiments are carried out under slope conditions to analyze chassis stability by testing plantar pressure. The results show that forest chassis using the barycenter control method helps keep stable on the slope of 15 degrees, much better than standard normal chassis.